Anti-Inflammatory Effects of the Novel Barbiturate Derivative MHY2699 in an MPTP-Induced Mouse Model of Parkinson's Disease - Seulah Lee; Yeon Ji Suh; Yujeong Lee; Seonguk Yang; Dong Geun Hong; Dinakaran Thirumalai; Seung-Cheol Chang; Ki Wung Chung; Young-Suk Jung; Hyung Ryong Moon; Hae Young Chung; Jaewon Lee (MDPI AG, 2021)
Parkinson's disease (PD) is one of the most common neurodegenerative disorders, and is caused by the death of dopamine neurons and neuroinflammation in the striatum and substantia nigra. Furthermore, the inflammatory response in PD is closely related to glial cell activation. This study examined the neuroprotective effects of the barbiturate derivative, MHY2699 [5-(4-hydroxy 3,5-dimethoxybenzyl)-2 thioxodihydropyrimidine-4,6(1H,5H)-dione] in a mouse model of PD. MHY2699 ameliorated MPP⁺-induced astrocyte activation and ROS production in primary astrocytes and inhibited the MPP⁺-induced phosphorylation of MAPK and NF-κB. The anti-inflammatory effects of MHY2699 in protecting neurons were examined in an MPTP-induced mouse model of PD. MHY2699 inhibited MPTP-induced motor dysfunction and prevented dopaminergic neuronal death, suggesting that it attenuated neuroinflammation. Overall, MHY2699 has potential as a neuroprotective treatment for PD.